2016
DOI: 10.1016/j.appet.2015.09.030
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous glucagon-like peptide-1 acts in sites supplied by the cranial mesenteric artery to reduce meal size and prolong the intermeal interval in rats

Abstract: Three experiments were done to better assess the gastrointestinal (GI) site(s) of action of GLP-1 on food intake in rats. First, near-spontaneous nocturnal chow meal size (MS), intermeal intervals (IMI) length and satiety ratios (SR = MS/IMI) were measured after infusion of saline, 0.025 or 0.5 nmol/kg GLP-1 into the celiac artery (CA, supplying the stomach and upper duodenum), cranial mesenteric artery (CMA, supplying small and all of the large intestine except the rectum), femoral artery (FA, control) or por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…The superior mesenteric artery (SMA) plays a vital role in supplying blood to the large part of the gastrointestinal tract (Williams et al, 2016), and plays a direct role in the pathophysiology of the intestinal motility disorders, absorption of nutrients, and blood pressure regulation (Fleming, 2000). It carries more than 10% of the systemic output (Crimi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The superior mesenteric artery (SMA) plays a vital role in supplying blood to the large part of the gastrointestinal tract (Williams et al, 2016), and plays a direct role in the pathophysiology of the intestinal motility disorders, absorption of nutrients, and blood pressure regulation (Fleming, 2000). It carries more than 10% of the systemic output (Crimi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…intra-arterial catheterization of the arteries of the gut, free feeding male rats, measuring eight feeding behaviors and measuring normal rat chow we have shown that the gastrointestinal tract contains sites of action controlling MS and IMI length by CCK-58 (Sayegh et al, 2015; Washington et al, 2016b), gastrin releasing peptide (Washington et al, 2014; Washington et al, 2016a) and glucagon like peptide-1 (Williams et al, 2016). The current study found that in free feeding male rats consuming normal chow the CA and the CMA supply sites of action regulating meal size reduction by CCK-8, whereas only the CMA supplies gastrointestinal sites of action regulating meal size reduction by CCK-33.…”
Section: Discussionmentioning
confidence: 99%
“…The catheterization procedures have been described in detail in our recent work (Sayegh et al, 2015; Washington et al, 2014; Washington et al, 2016a; Washington et al, 2016b; Williams et al, 2016). All catheters (Micro-Renathane Braintree Scientific R-ITC-SP 9.5) were 9.5" in length.…”
Section: Methodsmentioning
confidence: 99%
“…One catheter was implanted in each rat, and the meal patterns (meal was consumption of ≥ 0.2 g, and intermeal interval [IMI] was no feeding activity for ≥ 15 min), were done as described in details previously (Sayegh et al, 2015; Washington et al, 2014a; Washington et al, 2015; Williams et al, 2016). …”
Section: Methodsmentioning
confidence: 99%